Liver transplantation in pediatric patients under 15 kg; duct-to-duct vs. Roux-en-Y hepaticojejunostomy biliary anastomoses - S. M. Dehghani; M. Ataollahi; F. Salimi; K. Kazemi; S. Gholami; I. Shahramian; F. Parooie; M. Salarzaei; A. Aminisefat (Вестник трансплантологии и искусственных органов, 2021)
Back ground. Liver transplantation is an effective treatment for acute or chronic liver failure and metabolic liver disease, which is associated with good quality of life in over 80 percent of recipients. We aimed to evaluate outcome of duct-to-duct vs. Roux-en-Y hepaticojejunostomy biliary anastomoses in pediatric liver transplant recipients below 15-kg.Methods. In this single-center retrospective study, all children less than 15 kg that have undergone liver transplantation at Nemazee Hospital Organ Transplant Center affiliated with Shiraz University of Medical Sciences from 2009 till 2019, were enrolled. Over a 10-yr period, 181 liver transplants were performed in patients with two techniques including duct-to-duct (Group 1) vs. Roux-en-Y hepaticojejunostomy biliary anastomoses (Group 2). All data was collected from patients’ medical records, operative notes, and post-transplant follow up notes. Data was analyzed by SPSS software V21.Results. Overall, 94 patients had duct to duct anastomosis (group 1) and 87 cases had Roux-en-Y hepaticojejunostomy (group 2). The mean age of the patients was 2.46 ± 1.5. The most common underlying diseases was biliary atresia (32%). The most prevalent complication after the surgery was infection in both groups. cardiopulmonary problems were significantly higher in group 2 (24.1% vs 4.3%) (p < 0.001). The rate of infection was significantly higher in group 2, as well.Conclusion. Our study showed a relatively high rate of post-operative infection which was the most among patients who had undergone Roux-en-Y hepaticojejunostomy. Except from biliary complications which were mostly observed in DD group, other complications were more common among Roux-en-Y group.